Preparation method of zinc-nickel aerogel sensing material for detecting acetone
By mixing anhydrous zinc chloride and anhydrous nickel chloride in a mixed solution of anhydrous ethanol and purified water, and adding polyacrylic acid and propylene oxide, the zinc-nickel aerogel sensing material with high responsiveness and low detection limits is prepared, solving the problem that metal oxide semiconductor materials are prepared in the form of aerogel in the prior art is relatively rare.
Patent Information
- Application Number
- CN202411844081.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-15
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, there are fewer sensing materials for preparing metal oxide semiconductor materials into aerogel form, and fewer methods for preparing aerogel materials based on zinc oxide and nickel oxide.
By mixing anhydrous zinc chloride and anhydrous nickel chloride in a mixed solution of anhydrous ethanol and purified water, adding polyacrylic acid and propylene oxide, and after stirring, replacement, supercritical drying and calcining, zinc-nickel aerogel sensing material for detecting acetone was prepared.
The prepared zinc-nickel aerogel sensing material has high responsiveness and low detection limits to acetone, which fully exerts the high specific surface area and high porosity characteristics of the aerogel material.
Smart Images

Figure CN119637950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas sensor material preparation, and in particular to a method for preparing a zinc-nickel aerogel sensing material for detecting acetone. Background Art
[0002] In recent years, various metal oxide semiconductor materials have been widely used in the detection of acetone gas due to their advantages of high sensitivity, low cost, low power consumption and easy integration, and are expected to become the mainstream materials in this field.
[0003] However, there are only a handful of such metal oxide semiconductors that are made into aerogel-type sensing materials. They are generally prepared into sensing materials through traditional hydrothermal and electrospinning methods. The high specific surface area, high porosity, and low density of aerogel materials in their microstructure make this aspect not to be ignored and have great development potential. There are also very few methods for preparing aerogel materials based on zinc oxide and nickel oxide. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a zinc-nickel aerogel sensing material for detecting acetone, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a zinc-nickel aerogel sensing material for detecting acetone, comprising the following specific steps:
[0006] Step 1: Mix anhydrous ethanol and purified water in a certain ratio to obtain a first mixed solution, weigh anhydrous zinc chloride and add it to the first mixed solution to obtain a second mixed solution, weigh anhydrous nickel chloride and add it to the second mixed solution to obtain a first solution;
[0007] Step 2: Weigh polyacrylic acid and add it to the first solution to obtain a second solution;
[0008] Step 3: stirring the second solution, adding propylene oxide while stirring the second solution, and obtaining a precursor solution after stirring;
[0009] Step 4: putting the precursor solution into a container for gelation, adding anhydrous ethanol to the precursor solution after gelation, so that the anhydrous ethanol replaces the residual water and organic matter in the gel to obtain a wet gel;
[0010] Step 5: drying the replaced wet gel in a supercritical drying device using carbon dioxide;
[0011] Step six: calcining the dried gel to obtain zinc-nickel and zinc-cobalt aerogel sensing materials.
[0012] Preferably, in step 1, the mixing ratio of anhydrous ethanol to pure water is 1:1, the molar ratio of anhydrous zinc chloride to anhydrous nickel chloride is greater than or equal to 4:1, and the first solution is placed in a magnetic stirrer for stirring.
[0013] Preferably, the specific preparation steps of the first solution in step 1 are as follows:
[0014] Mix 15 ml of the anhydrous ethanol and 15 ml of the pure water, then weigh 3.20-4.00 g of the anhydrous zinc chloride and add it, and then weigh 0.70-0.88 g of the anhydrous nickel chloride and add it to obtain a first solution. Place the first solution in a magnetic stirrer under the following stirring conditions: stirring temperature of 20-30° C., stirring speed of 350-450 rpm, and stirring time of 10-30 min.
[0015] Preferably, the weight of the polyacrylic acid added in the step 2 is 2.00-6.00 g, and the obtained second solution is placed in a magnetic stirrer for stirring. The second solution is placed in the magnetic stirrer under the following stirring conditions: stirring temperature is 20-30° C., stirring speed is 350-450 rpm, and stirring time is 20-40 min.
[0016] Preferably, in step 3, the second solution is stirred and propylene oxide is added to obtain a precursor solution, and the specific preparation steps are as follows:
[0017] The second solution is placed on a magnetic stirrer for stirring, and 0.50-2.00 ml of propylene oxide is added to obtain a precursor solution. The second solution is placed on a magnetic stirrer for stirring under the following conditions: stirring temperature of 20-30° C., stirring speed of 350-450 rpm, and stirring time of 1.5-3 min.
[0018] Preferably, the specific steps of replacing the residual water and organic matter in the gel in step 4 are as follows:
[0019] Pour the precursor solution into an inverted syringe and wait for the precursor solution to gel. After gelation, push the colloid in the syringe into a beaker, then pour in anhydrous ethanol until it covers the colloid, and seal the beaker with plastic wrap. Replace the anhydrous ethanol every once in a while, and repeat this step 3-4 times to fully replace the residual water and organic matter in the gel.
[0020] Preferably, the precursor solution is placed in an inverted syringe and left to wait for gelation for 20-24 hours, and the anhydrous ethanol is replaced for 20-24 hours. This step is repeated 3-4 times to fully replace the residual water and organic matter in the gel.
[0021] Preferably, in step 5, carbon dioxide is used to dry the replaced wet gel in a supercritical drying device, comprising:
[0022] The replaced wet gel is dried using 1.5-3.0 L of carbon dioxide in a supercritical drying device at 11-13 MPa.
[0023] Preferably, the specific steps of calcining the dried gel in step 6 are as follows:
[0024] The dried aerogel is placed in a crucible, and then placed in a tubular furnace, calcined for a period of time, and when cooled to room temperature, zinc-nickel and zinc-cobalt aerogel sensing materials are obtained.
[0025] Preferably, the dried aerogel is placed in a crucible, then placed in a tubular furnace, calcined for a period of time, and when cooled to room temperature, a zinc-nickel aerogel sensing material is obtained, comprising:
[0026] The dried aerogel is placed in a crucible and then placed in a tubular furnace. The heating rate of the tubular furnace is set to 6-7°C / min, the calcination temperature is set to 450-550°C, and the calcination time is set to 1.5-3.0h. When cooled to room temperature, the zinc-nickel aerogel sensing material is obtained.
[0027] Technical effects and advantages of the present invention:
[0028] The invention utilizes a method for preparing a zinc-nickel aerogel sensing material for detecting acetone, mixes and dries the zinc-nickel aerogel sensing material, and then prepares the zinc-nickel aerogel sensing material for detecting acetone in a tubular furnace under an air atmosphere at a heating rate of 6-7°C / min, a calcination temperature of 500°C, and a calcination time of 2h. The prepared sensing material has the advantages of high response to acetone, low detection limit, and the like, and gives full play to the characteristics of high specific surface area and high porosity of the aerogel material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a flowchart of the present invention.
[0030] Figure 2 This is a physical picture of the zinc-nickel aerogel sensing material for detecting acetone after being supercritically dried with carbon dioxide.
[0031] Figure 3 This is the final morphology of the zinc-nickel aerogel sensing material for detecting acetone of the present invention.
[0032] Figure 4 This is a high response graph of the aerogel sensing material of the present invention to acetone. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The present invention provides Figure 1-4 A method for preparing a zinc-nickel aerogel sensing material for detecting acetone is shown.
[0035] Example 1
[0036] The specific steps include:
[0037] Step 1: Mix anhydrous ethanol and purified water in a certain ratio to obtain a first mixed solution, weigh anhydrous zinc chloride and add it to the first mixed solution to obtain a second mixed solution, weigh anhydrous nickel chloride and add it to the second mixed solution to obtain a first solution;
[0038] Step 2: Weigh polyacrylic acid and add it to the first solution to obtain a second solution;
[0039] Step 3: stirring the second solution, adding propylene oxide while stirring the second solution, and obtaining a precursor solution after stirring;
[0040] Step 4: putting the precursor solution into a container for gelation, adding anhydrous ethanol to the precursor solution after gelation, so that the anhydrous ethanol replaces the residual water and organic matter in the gel to obtain a wet gel;
[0041] Step 5: drying the replaced wet gel in a supercritical drying device using carbon dioxide;
[0042] Step 6: Calcine the dried gel to obtain zinc-nickel and zinc-cobalt aerogel sensing materials, refer to Figure 4 The obtained aerogel sensing material has high responses to 0.8ppm, 1ppm, and 10ppm acetone, and responds to 0.8ppm acetone, which shows that it has the advantage of a low detection limit. The response disappears after the acetone disappears, and it can respond again when the acetone reappears, giving full play to the high specific surface area and high porosity characteristics of the aerogel material.
[0043] Furthermore, in the step 1, the mixing ratio of anhydrous ethanol to pure water is 1:1, the molar ratio of anhydrous zinc chloride to anhydrous nickel chloride is 4:1, and the first solution is placed in a magnetic stirrer for stirring. The specific preparation steps of the first solution in the step 1 are as follows:
[0044] Mix 15 ml of the anhydrous ethanol and 15 ml of the pure water, then weigh 3.20 g of the anhydrous zinc chloride and add it, and then weigh 0.80 g of the anhydrous nickel chloride and add it to obtain a first solution. Place the first solution in a magnetic stirrer under the following stirring conditions: stirring temperature of 20° C., stirring speed of 350 rpm, and stirring time of 15 min.
[0045] Furthermore, the weight of the polyacrylic acid added in the step 2 is 3.00 g, and the obtained second solution is placed in a magnetic stirrer for stirring. The second solution is placed in the magnetic stirrer under the following stirring conditions: stirring temperature is 20° C., stirring speed is 350 rpm, and stirring time is 20 min.
[0046] Furthermore, in step 3, the specific preparation steps of stirring the second solution and adding propylene oxide to obtain a precursor solution are as follows:
[0047] The second solution was placed on a magnetic stirrer for stirring, and 0.60 ml of propylene oxide was added to obtain a precursor solution. The second solution was placed on a magnetic stirrer for stirring under the following conditions: stirring temperature was 20° C., stirring speed was 350 rpm, and stirring time was 1.5 min.
[0048] Furthermore, the specific steps of replacing the residual water and organic matter in the gel in step 4 are as follows:
[0049] The precursor solution is loaded into an inverted syringe and left to wait for the precursor solution to gel. After gelation, the colloid in the syringe is pushed into a beaker, and then anhydrous ethanol is poured until it covers the colloid, and the mouth of the beaker is sealed with plastic wrap. The anhydrous ethanol is replaced every once in a while, and this step is repeated 3-4 times to fully replace the remaining water and organic matter in the gel. The precursor solution is loaded into an inverted syringe and left to wait for gelation for 20 hours, and the anhydrous ethanol is replaced for 20 hours. This step is repeated 3-4 times to fully replace the remaining water and organic matter in the gel.
[0050] Furthermore, in step 5, carbon dioxide is used in a supercritical drying device to dry the replaced wet gel, comprising:
[0051] The replaced wet gel is dried using 1.5-3.0 L of carbon dioxide in a supercritical drying device at 11 MPa.
[0052] Furthermore, the specific steps of calcining the dried gel in step 6 are as follows:
[0053] The dried aerogel is placed in a crucible, and then placed in a tubular furnace and calcined for a period of time. When cooled to room temperature, zinc-nickel and zinc-cobalt aerogel sensing materials are obtained. The heating rate of the tubular furnace is set to 6-7°C / min, the calcination temperature is 450°C, the calcination time is 1.5h, and when cooled to room temperature, zinc-nickel aerogel sensing materials are obtained.
[0054] Embodiment 2 comprises the following specific steps:
[0055] Step 1: Mix anhydrous ethanol and purified water in a certain ratio to obtain a first mixed solution, weigh anhydrous zinc chloride and add it to the first mixed solution to obtain a second mixed solution, weigh anhydrous nickel chloride and add it to the second mixed solution to obtain a first solution;
[0056] Step 2: Weigh polyacrylic acid and add it to the first solution to obtain a second solution;
[0057] Step 3: stirring the second solution, adding propylene oxide while stirring the second solution, and obtaining a precursor solution after stirring;
[0058] Step 4: putting the precursor solution into a container for gelation, adding anhydrous ethanol to the precursor solution after gelation, so that the anhydrous ethanol replaces the residual water and organic matter in the gel to obtain a wet gel;
[0059] Step 5: drying the replaced wet gel in a supercritical drying device using carbon dioxide;
[0060] Step 6: Calcine the dried gel to obtain zinc-nickel and zinc-cobalt aerogel sensing materials, refer to Figure 4 The obtained aerogel sensing material has high responses to 0.8ppm, 1ppm, and 10ppm acetone, and responds to 0.8ppm acetone, which shows that it has the advantage of a low detection limit. The response disappears after the acetone disappears, and it can respond again when the acetone reappears, giving full play to the high specific surface area and high porosity characteristics of the aerogel material.
[0061] Furthermore, in the step 1, the mixing ratio of anhydrous ethanol to pure water is 1:1, the molar ratio of anhydrous zinc chloride to anhydrous nickel chloride is 5:1, and the first solution is placed in a magnetic stirrer for stirring. The specific preparation steps of the first solution in the step 1 are as follows:
[0062] Mix 15 ml of the anhydrous ethanol and 15 ml of the pure water, then weigh 3.95 g of the anhydrous zinc chloride and add it, and then weigh 0.79 g of the anhydrous nickel chloride and add it to obtain a first solution. Place the first solution in a magnetic stirrer under the following stirring conditions: stirring temperature of 26° C., stirring speed of 400 rpm, and stirring time of 20 min.
[0063] Furthermore, the weight of the polyacrylic acid added in the step 2 is 4.00 g, and the obtained second solution is placed in a magnetic stirrer for stirring. The second solution is placed in the magnetic stirrer under the following stirring conditions: stirring temperature is 36° C., stirring speed is 400 rpm, and stirring time is 30 min.
[0064] Furthermore, in step 3, the specific preparation steps of stirring the second solution and adding propylene oxide to obtain a precursor solution are as follows:
[0065] The second solution was placed on a magnetic stirrer for stirring, and 1.00 ml of propylene oxide was added to obtain a precursor solution. The second solution was placed on a magnetic stirrer for stirring under the following conditions: stirring temperature of 26° C., stirring speed of 400 rpm, and stirring time of 2 min.
[0066] Furthermore, the specific steps of replacing the residual water and organic matter in the gel in step 4 are as follows:
[0067] The precursor solution is loaded into an inverted syringe and left to wait for the precursor solution to gel. After gelation, the colloid in the syringe is pushed into a beaker, and then anhydrous ethanol is poured until it covers the colloid, and the mouth of the beaker is sealed with plastic wrap. The anhydrous ethanol is replaced every once in a while, and this step is repeated 3-4 times to fully replace the remaining water and organic matter in the gel. The precursor solution is loaded into an inverted syringe and left to wait for gelation for 24 hours, and the anhydrous ethanol is replaced for 24 hours. This step is repeated 3-4 times to fully replace the remaining water and organic matter in the gel.
[0068] Furthermore, in step 5, carbon dioxide is used in a supercritical drying device to dry the replaced wet gel, comprising:
[0069] The replaced wet gel was dried using 2.0 L of carbon dioxide in a supercritical drying device at 12 MPa.
[0070] Furthermore, the specific steps of calcining the dried gel in step 6 are as follows:
[0071] The dried aerogel is placed in a crucible, and then placed in a tubular furnace and calcined for a period of time. When cooled to room temperature, zinc-nickel and zinc-cobalt aerogel sensing materials are obtained. The heating rate of the tubular furnace is set to 6-7°C / min, the calcination temperature is 500°C, the calcination time is 2.0h, and when cooled to room temperature, zinc-nickel aerogel sensing materials are obtained.
[0072] Example 3
[0073] The specific steps include:
[0074] Step 1: Mix anhydrous ethanol and purified water in a certain ratio to obtain a first mixed solution, weigh anhydrous zinc chloride and add it to the first mixed solution to obtain a second mixed solution, weigh anhydrous nickel chloride and add it to the second mixed solution to obtain a first solution;
[0075] Step 2: Weigh polyacrylic acid and add it to the first solution to obtain a second solution;
[0076] Step 3: stirring the second solution, adding propylene oxide while stirring the second solution, and obtaining a precursor solution after stirring;
[0077] Step 4: putting the precursor solution into a container for gelation, adding anhydrous ethanol to the precursor solution after gelation, so that the anhydrous ethanol replaces the residual water and organic matter in the gel to obtain a wet gel;
[0078] Step 5: drying the replaced wet gel in a supercritical drying device using carbon dioxide;
[0079] Step 6: Calcine the dried gel to obtain zinc-nickel and zinc-cobalt aerogel sensing materials, refer to Figure 4 The obtained aerogel sensing material has high responses to 0.8ppm, 1ppm, and 10ppm acetone, and responds to 0.8ppm acetone, which shows that it has the advantage of a low detection limit. The response disappears after the acetone disappears, and it can respond again when the acetone reappears, giving full play to the high specific surface area and high porosity characteristics of the aerogel material.
[0080] Furthermore, in the step 1, the mixing ratio of anhydrous ethanol to pure water is 1:1, the molar ratio of anhydrous zinc chloride to anhydrous nickel chloride is greater than 4:1, and the first solution is placed in a magnetic stirrer for stirring. The specific preparation steps of the first solution in the step 1 are as follows:
[0081] Mix 15 ml of the anhydrous ethanol and 15 ml of the pure water, then weigh 4.00 g of the anhydrous zinc chloride and add it, and then weigh 0.88 g of the anhydrous nickel chloride and add it to obtain a first solution. Place the first solution in a magnetic stirrer under the following stirring conditions: stirring temperature of 30° C., stirring speed of 450 rpm, and stirring time of 30 min.
[0082] Furthermore, the weight of the polyacrylic acid added in the step 2 is 6.00 g, and the obtained second solution is placed in a magnetic stirrer for stirring. The second solution is placed in the magnetic stirrer under the following stirring conditions: stirring temperature is 30° C., stirring speed is 450 rpm, and stirring time is 40 min.
[0083] Furthermore, in step 3, the specific preparation steps of stirring the second solution and adding propylene oxide to obtain a precursor solution are as follows:
[0084] The second solution was placed on a magnetic stirrer for stirring, and 2.00 ml of propylene oxide was added to obtain a precursor solution. The second solution was placed on a magnetic stirrer for stirring under the following conditions: stirring temperature of 30° C., stirring speed of 450 rpm, and stirring time of 3 min.
[0085] Furthermore, the specific steps of replacing the residual water and organic matter in the gel in step 4 are as follows:
[0086] The precursor solution is loaded into an inverted syringe and left to wait for the precursor solution to gel. After gelation, the colloid in the syringe is pushed into a beaker, and then anhydrous ethanol is poured until it covers the colloid, and the mouth of the beaker is sealed with plastic wrap. The anhydrous ethanol is replaced every once in a while, and this step is repeated 3-4 times to fully replace the remaining water and organic matter in the gel. The precursor solution is loaded into an inverted syringe and left to wait for gelation for 22 hours, and the anhydrous ethanol is replaced for 22 hours. This step is repeated 3-4 times to fully replace the remaining water and organic matter in the gel.
[0087] Furthermore, in step 5, carbon dioxide is used in a supercritical drying device to dry the replaced wet gel, comprising:
[0088] The replaced wet gel was dried using 3.0 L of carbon dioxide in a supercritical drying device at 13 MPa.
[0089] Furthermore, the specific steps of calcining the dried gel in step 6 are as follows:
[0090] The dried aerogel is placed in a crucible, and then placed in a tubular furnace and calcined for a period of time. When cooled to room temperature, zinc-nickel and zinc-cobalt aerogel sensing materials are obtained. The heating rate of the tubular furnace is set to 6-7°C / min, the calcination temperature is 550°C, the calcination time is 3.0h, and when cooled to room temperature, zinc-nickel aerogel sensing materials are obtained.
[0091] In summary, anhydrous zinc chloride and anhydrous nickel chloride are mixed in a solution of anhydrous ethanol and pure water in a molar ratio of greater than or equal to 4:1, polyacrylic acid is added in a molar ratio of greater than or equal to 1:10 to anhydrous zinc chloride, and then propylene oxide is added in a molar ratio of greater than or equal to 1:2 to anhydrous zinc chloride, and dried in a 2L carbon dioxide supercritical drying device, and finally a zinc-nickel aerogel sensing material with the ability to detect acetone is prepared in a tubular furnace under an air atmosphere at a heating rate of 6-7°C / min, a calcination temperature of 500°C, and a calcination time of 2h. The prepared sensing material has the advantages of high response to acetone and low detection limit, and gives full play to the characteristics of high specific surface area and high porosity of the aerogel material. The actual zinc-nickel aerogel sensing material after supercritical carbon dioxide drying is as follows Figure 2As shown in FIG. 1 , which is a physical picture of the aerogel produced through steps S101 to S105, the final morphology of the zinc-nickel aerogel sensing material for detecting acetone is as follows Figure 3 As shown, that is Figure 2 The sensing material diagram obtained after step S106 is shown.
[0092] The terms "first", "second", "third" and "fourth" etc. in the specification and claims of the present application and the drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0093] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0094] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a zinc-nickel aerogel sensing material for detecting acetone, characterized in that: The specific steps include: Step 1: Mix anhydrous ethanol and purified water in a certain ratio to obtain a first mixed solution, weigh anhydrous zinc chloride and add it to the first mixed solution to obtain a second mixed solution, weigh anhydrous nickel chloride and add it to the second mixed solution to obtain a first solution; Step 2: Weigh polyacrylic acid and add it to the first solution to obtain a second solution; Step 3: stirring the second solution, adding propylene oxide while stirring the second solution, and obtaining a precursor solution after stirring; Step 4: putting the precursor solution into a container for gelation, adding anhydrous ethanol to the precursor solution after gelation, so that the anhydrous ethanol replaces the residual water and organic matter in the gel to obtain a wet gel; Step 5: drying the replaced wet gel in a supercritical drying device using carbon dioxide; Step six: calcining the dried gel to obtain zinc-nickel and zinc-cobalt aerogel sensing materials.
2. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 1, characterized in that: In the step 1, the mixing ratio of anhydrous ethanol to pure water is 1:1, the molar ratio of anhydrous zinc chloride to anhydrous nickel chloride is greater than or equal to 4:1, and the first solution is placed in a magnetic stirrer for stirring.
3. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 2, characterized in that: The specific preparation steps of the first solution in step 1 are as follows: Mix 15 ml of the anhydrous ethanol and 15 ml of the pure water, then weigh 3.20-4.00 g of the anhydrous zinc chloride and add it, and then weigh 0.70-0.88 g of the anhydrous nickel chloride and add it to obtain a first solution. Place the first solution in a magnetic stirrer under the following stirring conditions: stirring temperature of 20-30° C., stirring speed of 350-450 rpm, and stirring time of 10-30 min.
4. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 1, characterized in that: The weight of the polyacrylic acid added in the step 2 is 2.00-6.00 g, and the obtained second solution is placed in a magnetic stirrer for stirring. The second solution is placed in the magnetic stirrer under the following stirring conditions: stirring temperature is 20-30° C., stirring speed is 350-450 rpm, and stirring time is 20-40 min.
5. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 1, characterized in that: In the step 3, the second solution is stirred and propylene oxide is added to obtain a precursor solution. The specific preparation steps are as follows: The second solution is placed on a magnetic stirrer for stirring, and 0.50-2.00 ml of propylene oxide is added to obtain a precursor solution. The second solution is placed on a magnetic stirrer for stirring under the following conditions: stirring temperature of 20-30° C., stirring speed of 350-450 rpm, and stirring time of 1.5-3 min.
6. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 1, characterized in that: The specific steps of replacing the residual water and organic matter in the gel in step 4 are as follows: Pour the precursor solution into an inverted syringe and wait for the precursor solution to gel. After gelation, push the colloid in the syringe into a beaker, then pour in anhydrous ethanol until it covers the colloid, and seal the beaker with plastic wrap. Replace the anhydrous ethanol every once in a while, and repeat this step 3-4 times to fully replace the residual water and organic matter in the gel.
7. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 6, characterized in that: The precursor solution is placed in an inverted syringe and left to wait for gelation for 20-24 hours, and the time for replacing with anhydrous ethanol is 20-24 hours. This step is repeated 3-4 times to fully replace the residual water and organic matter in the gel.
8. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 1, characterized in that: In the step 5, carbon dioxide is used in a supercritical drying device to dry the replaced wet gel, including: The replaced wet gel is dried using 1.5-3.0 L of carbon dioxide in a supercritical drying device at 11-13 MPa.
9. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 1, characterized in that: The specific steps of calcining the dried gel in step 6 are as follows: The dried aerogel is placed in a crucible, and then placed in a tubular furnace, calcined for a period of time, and when cooled to room temperature, zinc-nickel and zinc-cobalt aerogel sensing materials are obtained.
10. The method for preparing a zinc-nickel aerogel sensing material for detecting acetone according to claim 9, characterized in that: The dried aerogel is placed in a crucible, and then placed in a tubular furnace, calcined for a period of time, and when cooled to room temperature, a zinc-nickel aerogel sensing material is obtained, including: The dried aerogel is placed in a crucible and then placed in a tubular furnace. The heating rate of the tubular furnace is set to 6-7°C / min, the calcination temperature is set to 450-550°C, and the calcination time is set to 1.5-3.0h. When cooled to room temperature, the zinc-nickel aerogel sensing material is obtained.